Midwifery Care for Pregnant Women Mrs. A G1p0a0 With Abortion Imminens At Siti Kholijah Clinic, Medan Marelan in 2019 - Devi Susana Pinem; Putri Ramadani; Nurainun; Intan Agustin (Science Midwifery, 2019)
The main causes of maternal death in Indonesia have not changed much, namely bleeding, eclampsia, complications of abortion, obstructed labor and sepsis. Bleeding, which is responsible for about 28% of maternal deaths, is often unpredictable and occurs suddenly. Most bleeding occurs postpartum, either due to uterine atony or retained placenta. This shows that the handling of the third stage is less than optimal and the failure of the health care system to handle obstetric and neonatal emergencies quickly and accurately.Carry out midwifery care for pregnant women withabortion imminenswhich uses Varney's 7-step management process. The author is able to analyze the gap between theory and real cases in the field. The author is able to provide alternative solutions to problems. Type of case study report with descriptive method, location in Sisti Kholijah Maternity Clinic. The subject of the case study Mrs. A pregnant withabortion imminens, the time of the case study on March 10-13, 2015. Data collection techniques include primary data, including physical examination, interviews and observations and secondary data, including documentation studies and literature studies. Mrs. A, G1 P0 A0 30 years pregnant 13 weeks 2 days withabortion imminens. Drug therapy Preabor 50 mg 3 x 1, Mefenamic acid 500 mg 3 x 1, Folic acid 400 mg 2 x 1 and RL 20 infusion. The mother's general condition is good, composmentis consciousness, the mother does not feel anxious anymore, discharge brown spots has stopped, no potential occursabortion insipiensas well asabortiondoes not continue and the mother's pregnancy can still be maintained.In the case of Mrs. There is a gap between theory and practice, namely in the planning and implementation steps, namely in practice it is recommended to eat nutritious food and personal hygiene.